IMPLIKASI NILAI BUDAYA HAMORAON, HAGABEON DAN HASANGAPON MENUMBUHKAN SIKAP DAN MOTIVASI BERWIRAUSAHA ETNIS BATAK DI KOTA BANDAR LAMPUNG - Simbolon, Rinaldo; Efendi, Nur; Adistya, Diang (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2024)
The purpose of this study is to explore and analyze the attitudes and motivations of Batak ethnic in entrepreneurship in Bandar Lampung City. This type of research is descriptive with a qualitative approach. The technique of selecting informants using purposive method and determining the number of informants using snowball sampling technique. The data collection techniques used were in-depth interviews, observation, and documentation. The data analysis technique uses interactive model data analysis, and the data validity technique uses source triangulation. The results of this study indicate that the attitudes shown by ethnic Batak in carrying out entrepreneurial activities are disciplined, highly committed, honest, creative and innovative, independent and realistic. While the motivational factors of ethnic Batak in entrepreneurship are profit, freedom, personal dreams and independence. The findings in this study indicate that the 3H cultural value can directly influence Batak people in carrying out entrepreneurial activities. The existence of the Hamoraon, Hagabeon and Hasangapon philosophies helped foster their attitudes and motivations. In realizing these cultural values, it makes them have a high work ethic, hardworking, unyielding, high enthusiasm and competitive spirit in achieving their goals.